Free and pulsed jet rotational spectra and van der Waals motions of ethanol center dot center dot center dot argon - Maris, A; Caminati, W; Velino, B; Andrews, C; Howard, B (2004)
The rotational spectrum of the ethanol⋯argon van der Waals complex has been investigated by free-jet absorption millimeter-wave and molecular beams Fourier transform microwave spectroscopy. The spectra of normal and OD isotopomers have been assigned, but only for the complex with trans-ethanol. Ar motions produce vibrational splittings of 1.6662(7) and 1.70(2) MHz for the two isotopic species, respectively. The barrier hindering the tunnelling motion has been evaluated to be about 55 cm -1. The van der Waals structural parameters are: r 0(Ar-O) = 3.56(1) Å, α 0(〈ArOC) = 94°(1) and τ 0(〈ArOCC) = 71°(1). The dissociation energy, as obtained from centrifugal distortion effects, is 2.1 kJ mol -1. © 2004 Elsevier B.V. All rights reserved.